Effect of Vitamin E dan C Supplementation In Feed on Carcass Abdominal Fat and Meat Fat Percentage of Muscovy Duck - Tugiyanti, Elly; Yuwanta, Tri; Zuprizal, Zuprizal; Rusman, Rusman (Indonesian Society of Animal Science in collaboration with Indonesian Ministry of Agriculture and Faculty of Animal Science UGM, 2014)
This study was conducted to evaluate the effect of Vitamin E and C Supplementation in feed on carcass, abdominal fat and meat fat percentage of Muscovy duck. Eighty four male Muscovy ducks were alloted into seven treatments, namely A0, diet without supplemented vitamin E and C; A1, diet supplemented with 400 IU of vitamin E; A2, diet supplemented with 600 IU of vitamin E; A3, diet supplemented with 400 mg of vitamin C; A4, diet supplemented with 600 mg of vitamin C; A5, diet supplemented with 200 IU of vitamin E and vitamin C; each with three repetitions. The result showed that treatments did not significantly affect (P>0.05) on the percentage of carcass, abdominal fat and meat fat. In conclusion, supplementation of vitamin E to the level of 600 IU and vitamin C to 600 mg or a combination of vitamin E to the level 300 IU and 300 mg have not yet been able to increase the production of Muscovy duck carcass and decrease the abdominal fat and fatty meat.